On the Construction of Common Size, Value and Momentum Factors in International Stock Markets: A Guide with Applications - Peter S. Schmidt; Urs von Arx; Andreas Schrimpf; Alexander F. Wagner; Andreas Ziegler (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
Demand is growing for a better understanding of how assets are priced in countries outside of the U.S. While financial data are available for many firms world-wide, it is important to have a reliable and replicable method of constructing high-quality systematic risk factors from these data. This paper first documents that appropriately screened data from Thomson Reuters Datastream and Thomson Reuters Worldscope can be used to replicate closely not only U.S. market returns and the corresponding momentum risk factor (as existing work has suggested), but also the widely-used U.S. size and value risk factors. We then build novel pan-European and country-specific momentum, size, and value risk factors. By comparing our pan-European market returns and risk factors with their counterparts in the U.S., we find that they are astonishingly highly correlated. The factors we compute are made available to other researchers.
Keywords: C89; G12; G15; 330; Risk factors; value; size; momentum; international equity markets; asset pricing anomalies; Börsenkurs; Risikomaß; Kapitaleinkommen; Volatilität; Spillover-Effekt; Vergleich; Europa; USA